Increasing Capacity For Conservation Of Threatened Fish Species Through Data Mobilization And Training (BID-AF 2017-0206-SMA) - Natugonza, Vianny; Musinguzi, Laban (Biodiversity Informatics, 2017)
Despite presence of huge biodiversity data on primary species occurrence records available through the Global Biodiversity Information Facility (GBIF), more data remains inaccessible while policy formulation in some countries still does not directly benefit from mobilized data. This is because many institutions have not published their data and, in most cases, data are mobilized without a prior understanding of the needs of the users, respectively. With support from the European Union, GBIF, and the National Fisheries Resources Research Institute (NaFIRRI), NaFIRRI intends to mobilize at least 10,000 fish records and create a first—ever—comprehensive dataset of fish species occurrence in Uganda with most up—to—date information. To ensure that mobilized data directly benefits policy makers, data needs and mapping surveys were undertaken to assess the user specific needs for fish biodiversity data as well as identify data holding institutions. Data on species occurrences, especially in highly vulnerable ecosystems that are faced with multiple stressors, as well as data limited ecosystems got high ranking. Policy makers also need data presented in easily comprehensible formats, such distribution maps, checklists, graphs, and factsheets or policy briefs. Five data holding institutions and some individuals willing to share fish biodiversity data with NaFIRRI were identified. The identified data needs will guide development of user—driven data format for mobilizing and presenting fish biodiversity data in Uganda, while the data holding institutions will be engaged to ensure that their data is published.